Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am doing an Algebra course (UC Irvine / Coursera), and am having a bit of trouble understanding the following property:

$$ 3(x+h)^2 $$

Seems to be distributed as such:

$$ 3(x^2+2xh+h^2) $$

.. now, due to the distributive property, I understand why the $x^2$ and $h^2$ are so, but I have no idea where the "extra" $2xh$ came from. I've been grappling with the fact that while the original quantity can be represented as,

$$ 3(x+h)(x+h) $$

..it's just not clear to me how the $2xh$ is "created".

Any advice on this would be appreciated.

NB: This is not an assignment; it's from Week 2, Lecutre "Multiple Operations with Polynomials", at about 5:30.

Thanks!

sc.

share|improve this question

2 Answers 2

up vote 3 down vote accepted

Note that addition distributes over multiplication so

$$(x + h)^2 = (x+h)(x+h) = x(x+h)+h(x+h).$$

Now note that multiplication distributes over addition, so

$$x(x + h) = x\cdot x + xh = x^2 + xh$$

and

$$h(x+h) = hx + h\cdot h = hx + h^2.$$

Combining, we have

$$(x+h)^2 = x^2 + xh + hx + h^2.$$

Finally, note that multiplication is commutative so $hx = xh$ and hence

$$(x+h)^2 = x^2 + xh + hx + h^2 = x^2 + xh + xh + h^2 = x^2 + 2xh + h^2.$$

share|improve this answer
3  
Great, thanks! It seems that I neglected to recall the FOIL method. I've been "FOIL'd again" ! –  swisscheese Feb 16 '13 at 14:03

$(x+h)(x+h)=x(x+h)+h(x+h)=\\ =x\cdot x+x\cdot h+h\cdot x+h\cdot h=\\ =x^2+xh+hx+h^2=\\ =x^2+2xh+h^2$

$2xh$ is created from $xh$ and $hx$.

share|improve this answer
    
Thank you for your answer - a great complement to the above answer! –  swisscheese Feb 16 '13 at 14:04

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.